Yoga as a Comprehensive Therapy for Reducing Cancer- Related Fatigue: A Comprehensive Review - B S, Anantha Krishna; Sheelam, Praveen K (Asian Pacific Journal of Cancer Care, 2024)
Objective: This comprehensive review aimed to explore the efficacy of yoga as a comprehensive therapy for reducing cancer-related fatigue. The objective was to delve into the biological mechanisms, psychological effects, and clinical evidence supporting the impact of yoga on fatigue in cancer patients. Material and methods: A systematic literature search was conducted across various databases, including PubMed, Google Scholar, and relevant journals. The review encompasses studies focusing on the intersection of yoga and cancer-related fatigue. Results: This review provided a thorough examination of how yoga can serve as a comprehensive therapy for cancer-related fatigue. Biological mechanisms, including neuroendocrine modulation, immune system influence, and inflammation regulation, were discussed. Psychological mechanisms, such as stress reduction and mood improvement, were explored. The analysis included a diverse range of clinical evidence, incorporating randomized controlled trials and observational studies. Conclusion: This comprehensive review consolidates evidence supporting yoga as a holistic intervention for reducing cancer-related fatigue. By addressing both the biological and psychological dimensions, the review underscores the potential of yoga in offering a comprehensive approach to alleviate fatigue in the context of cancer care.